Radiopharmaceuticals: navigating the frontier of precision medicine and therapeutic innovation - Shivang Dhoundiyal; Shriyansh Srivastava; Sachin Kumar; Gaaminepreet Singh; Sumel Ashique; Radheshyam Pal; Neeraj Mishra; Farzad Taghizadeh‐Hesary (2024)
This review article explores the dynamic field of radiopharmaceuticals, where innovative developments arise from combining radioisotopes and pharmaceuticals, opening up exciting therapeutic possibilities. The in-depth exploration covers targeted drug delivery, delving into passive targeting through enhanced permeability and retention, as well as active targeting using ligand-receptor strategies. The article also discusses stimulus-responsive release systems, which orchestrate controlled release, enhancing precision and therapeutic effectiveness. A significant focus is placed on the crucial role of radiopharmaceuticals in medical imaging and theranostics, highlighting their contribution to diagnostic accuracy and image-guided curative interventions. The review emphasizes safety considerations and strategies for mitigating side effects, providing valuable insights into addressing challenges and achieving precise drug delivery. Looking ahead, the article discusses nanoparticle formulations as cutting-edge innovations in next-generation radiopharmaceuticals, showcasing their potential applications. Real-world examples are presented through case studies, including the use of radiolabelled antibodies for solid tumors, peptide receptor radionuclide therapy for neuroendocrine tumors, and the intricate management of bone metastases. The concluding perspective envisions the future trajectory of radiopharmaceuticals, anticipating a harmonious integration of precision medicine and artificial intelligence. This vision foresees an era where therapeutic precision aligns seamlessly with scientific advancements, ushering in a new epoch marked by the fusion of therapeutic resonance and visionary progress.